O ensino remoto e práticas docentes na educação básica em tempos de pandemia - SILVA, Edna Maria dos Santos da (2024)
In the current context of education, with the sudden change in the form of teaching that went from classroom to remote teaching, it is necessary to investigate the changes that have occurred in the pedagogical practices of teachers in the public school system. In this sense, we raise the following question: in what terms do teachers express perceptions in relation to their educational practices in times of pandemic? The objective was to understand the perceptions about the practices of teachers in this scenario, in addition to explaining the educational practices during the pandemic period, the difficulties encountered and the solutions adopted. I assume the Narrative Research, having as object, the testimonies of three Basic Education teachers from the municipal school system of Belém, expressed through semi-structured interviews, carried out via digital applications. Such interviews constitute the corpus of the research that was analyzed through discursive textual analysis. In the teachers' perceptions, remote teaching, like face-toface teaching, can only be developed in its entirety with direct contact between students and teacher, and that this lack of contact combined with a deficit of access to digital technologies (smartphone and internet), contributed to the regression in the development of student learning.